The infrapatellar fat pad is a dynamic and mobile structure, which deforms during knee motion, and has proximal extensions which wrap around the patella - Stephen,JM; Sopher,R; Tullie,S; Amis,AA; Ball,S; Williams,A (Knee Surgery, Sports Traumatology, Arthroscopy, 2018)
PURPOSE: The infrapatellar fat pad (IFP) is a common cause of knee pain and loss of knee flexion and extension. However, its anatomy and behavior are not consistently defined. METHODS: Thirty-six unpaired fresh frozen knees (median age 34 years, range 21-68) were dissected, and IFP attachments and volume measured. The rectus femoris was elevated, suprapatellar pouch opened and videos recorded looking inferiorly along the femoral shaft at the IFP as the knee was flexed. The patellar retinacula were incised and the patella reflected distally. The attachment of the ligamentum mucosum (LMuc) to the intercondylar notch was released from the anterior cruciate ligament (ACL), both menisci and to the tibia via meniscotibial ligaments. IFP strands projecting along both sides of the patella were elevated and the IFP dissected from the inferior patellar pole. Magnetic resonance imaging (MRI) of one knee at ten flexion angles was performed and the IFP, patella, tibia and femur segmented. RESULTS: In all specimens the IFP attached to the inferior patellar pole, femoral intercondylar notch (via the LMuc), proximal patellar tendon, intermeniscal ligament, both menisci and the anterior tibia via the meniscotibial ligaments. In 30 specimens the IFP attached to the anterior ACL fibers via the LMuc, and in 29 specimens it attached directly to the central anterior tibia. Proximal IFP extensions were identified alongside the patella in all specimens and visible on MRI [medially (100% of specimens), mean length 56.2 ± 8.9 mm, laterally (83%), mean length 23.9 ± 6.2 mm]. Mean IFP volume was 29.2 ± 6.1 ml. The LMuc, attached near the base of the middle IFP lobe, acting as a 'tether' drawing it superiorly during knee extension. The medial lobe consistently had a pedicle superomedially, positioned between the patella and medial trochlea. MRI scans demonstrated how the space between the anterior tibia and patellar t